A Review on Blind Bolt Connection to Concrete Filled Hollow Section Under Cyclic Load - Mohd Azlan, Muhammad Nurhisham; Abd Rahman, Norashidah (Recent Trends in Civil Engineering and Built Environment, 2021)
Research on the blind bolt is currently being extended to the use of concrete filled hollow section to increase the overall strength of steel structures. However, information into blind bolted connection of concrete-filled hollow sections (CFHS) under cyclic loading remains ongoing. The objectives of this study is to review on different type of bolt connection and to analyze the strength of the different type of blind bolt to CHFS under cyclic load. The information is obtained from literature review through reading of journals, books, and other sources. It can be concluded that for the first objectives of this review paper, the blind bolts that are reviewed in this study are Extended Hollobolt, Slip Critical Blind Bolt and Double Headed Anchored Blind Bolt. For the second objective, it is concluded that the strength of the blind bolt show an acceptable figure assessment. This was proven by the ultimate tensile strength of the entire three blind bolts in this review paper with the Extended Hollobolt obtaining 852.39 MPa, the Slip Critical Blind Bolt achieving 918.18 MPa and the Double Headed Anchored Blind bolt achieving 925 Mpa in ultimate tensile strength.